2010
DOI: 10.1002/cjce.20275
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield synthesis of multi‐walled carbon nanotube by hydrothermal method

Abstract: The evolution of multi-walled carbon nanotubes (MWCNTs) under hydrothermal condition was investigated, because the hydrothermal method (HTM) has been utilised for commercial production of advanced engineering materials. To synthesise MWCNTs by hydrothermal process using mixed aqueous solution diethylenetriamine, polyethyleneglycol (PEG) and NaOH were used as starting materials. We investigated the effect of hydrothermal temperature, time, and amount of formative compounds. Hydrothermal reaction temperature was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Raman spectroscopy is widely used for the characterization of carbonaceous materials because it is sensitive to both crystal structure and molecular structure . Raman spectra of carbonaceous materials can be divided into two regions: the first‐order region and the second‐order region.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is widely used for the characterization of carbonaceous materials because it is sensitive to both crystal structure and molecular structure . Raman spectra of carbonaceous materials can be divided into two regions: the first‐order region and the second‐order region.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [18] reported that the hydrothermally synthesized graphene exhibited high electrical conductivity (5 mS cm -1 ) as well as better specific capacitance of 175 F g -1 at a scan rate of 10 mV s -1 . Moreover, Manafi et al [19] successfully synthesized multi-walled carbon nanotubes (MWCNTs) via the hydrothermal method without using catalysts.…”
Section: Carbonaceous Materialsmentioning
confidence: 99%
“…Recently, many researchers have used hydrothermal synthesis at low temperatures because of its energy-saving property and simple synthesis. Manafi et al [ 42 ] used an easy sonochemical/hydrothermal method at 160 °C. Funke et al [ 43 ] used elevated temperatures (180–220 °C) for biomass in a water suspension under saturated pressure for a few hours.…”
Section: Introductionmentioning
confidence: 99%